2022
DOI: 10.1111/pbr.13000
|View full text |Cite
|
Sign up to set email alerts
|

Why is rice Amax (at saturating CO2) more heritable than Asat (at ambient CO2)? A commentary on Acevedo‐Siaca et al. (2021)

Abstract: Acevedo‐Siaca et al. (2021) reported that Amax (at saturating CO2) is more heritable than Asat (at ambient CO2) in rice and suggested the former to be selected to improve photosynthesis under rising ambient [CO2] levels. This commentary hypothesizes sink limitation to be a factor contributing to low genotypic Amax via feedback inhibition (acclimation) of photosynthesis as observed under elevated [CO2]. This process may to some extent also happen under current ambient [CO2]. If confirmed, future breeding for gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Measurement error ( Gu et al , 2012a ) and the uncertainty in innate reasons for observed variability of photosynthesis ( Fabre and Dingkuhn, 2022 ) might explain why its variation remains poorly explained. However, this does not mean that there is little opportunity to improve photosynthesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Measurement error ( Gu et al , 2012a ) and the uncertainty in innate reasons for observed variability of photosynthesis ( Fabre and Dingkuhn, 2022 ) might explain why its variation remains poorly explained. However, this does not mean that there is little opportunity to improve photosynthesis.…”
Section: Discussionmentioning
confidence: 99%
“… Acevedo-Siaca et al (2021) showed that like V cmax and J max , T p estimated for 30 rice accessions had high heritability. Data of Acevedo-Siaca et al (2021) further showed that rice A max at CO 2 saturation was highly heritable but A max at ambient [CO 2 ] was not, suggesting that genotypic variation in A max might be caused by genotypic sink limitation ( Fabre and Dingkuhn, 2022 ).…”
Section: Natural Variation Of Photosynthetic Parametersmentioning
confidence: 99%
“…Lastly, it should be noted that sink-source relations exist also during vegetative growth and affect pre-floral biomass accumulation under e-CO 2 conditions (Dingkuhn et al, 2021). For example, genotypic tillering potential has been shown to contribute positively to crop e-CO 2 response in rice (Ziska et al, 2013;Kadam et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…It is becoming increasingly evident that ignoring TPU in situations of source-sink imbalance can cause errors when modeling crop photosynthesis (Sharkey, 2019;Yin et al , 2021) A consequence of these findings is that A max is not solely determined by constitutive properties of the photosynthetic apparatus of a given plant, in which case its value would be constant during the day. Instead, A max decreases throughout the day, particularly when the local carbon source-sink ratio is high (Fabre and Dingkuhn, 2022). This indicates that maintaining highA max requires efficient evacuation of photosynthates from the leaves.…”
Section: Introductionmentioning
confidence: 99%